A new efficient Rabin-like signature scheme - Mahad, Zahari; Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this work, we present a new Rabin-like signature scheme. This new scheme does not utilize Legendre and Jacobi symbols. It also does not use extra information either during signing or verification process. We name this scheme as the Rabin-RZ signature scheme.